Plerixafor in combination with granulocyte–colony‐stimulating factor after chemotherapy increases mobilization efficiency in patients with lymphoma or myeloma: results of a Phase II clinical trial. Issue 10 (2nd September 2015) - Jagirdar, Neera; Harvey, R. Donald; Nooka, Ajay; Flowers, Christopher; Kaufman, Jonathan; Lonial, Sagar; Lechowicz, Mary Jo; Langston, Amelia; Lipscomb, Carol; Gaylor, Cynthia; Waller, Edmund K.
<x xml:space="preserve">Abstract</x> BACKGROUND We tested whether adding plerixafor to G‐CSF mobilization after chemotherapy would increase the proportion of patients collecting the target number of CD34+ cells/kg in 1 day of apheresis to >75%. STUDY DESIGN AND METHODS Autologous stem cell transplant–anticipated multiple myeloma or lymphoma patients were eligible. Patients were mobilized with cyclophosphamide (n=17); DCEP (n=1); R‐ICE (n=20); CHOP (n=2); or R‐HCVAD (n=5) and given 5 mg/kg/day GCSF starting on Day 2 and increasing to 10 mg/kg/day on Day 6. Plerixafor 240 mg/kg was injected subcutaneously on the day the neutrophil count was more than 1.5 × 109 cells/L with apheresis the folllowing day. G‐CSF, plerixafor, and apheresis continued daily until 5 × 106 (lymphoma) or 10 × 106 (myeloma) CD34+ cells/kg were collected. RESULTS Seventeen myeloma and 28 lymphoma patients enrolled, and 76% collected the target number of CD34+ cells in 1 day. Twelve subjects with median CD34+ counts of 142 × 106 cells/L began apheresis without plerixafor and collected 20 × 106 CD34+ cells/kg in 1 day. The remaining 33 subjects, with median 11.7 × 106 CD34+ cells/L and 5.4 × 109 WBC/L, received plerixafor. Plerixafor‐treated subjects collected 7.8 × 106 CD34+ cells/kg; 22 (67%) collected in 1 day, while 11 (33%) required more than 1 day. Plerixafor was well tolerated, with no serious adverse events. CONCLUSIONS Plerixafor administration after chemotherapy for autologous stem cell mobilization is feasible, well tolerated, and increases the proportion of subjects collected in a single day compared to mobilization with G‐CSF after chemotherapy.